Anxiety faintly and depression remarkably correlate with recurrence in acute ischemic stroke patients: A study with 3-year longitude evaluation and follow-up. Issue 3 (21st January 2022) - Luan, Shaoqun; Wu, Xin; Yin, Shaohua
Abstract : Abstract: Clinical value of anxiety and depression in acute ischemic stroke (AIS) is rarely studied. Thus, the aim of this study was to explore longitudinal changes of anxiety and depression, as well as their correlation with recurrence in AIS. A total of 120 AIS patients and 120 controls were enrolled in the study. Furthermore, comparison of the hospital anxiety and depression scale (HADS) score or rate between AIS and controls was determined by Mann–Whitney U test or Chi-square test. In AIS patients, change of HADS scores or linear trend of anxiety and depression rate over time were determined by Friedman test or Mantel-Haenszel Chi-square test. Moreover, correlation of anxiety and depression with the recurrence rate was analyzed by log-rank test. HADS for anxiety score, anxiety rate, HADS for depression score and depression rate were all elevated in AIS patients compared with controls (all P  < .001). In AIS patients, HADS for anxiety score was elevated from discharged from hospital (M0) to month (M) 36 ( P  = .027), while anxiety rate was not ( P  = .107). Besides, HADS-D score and rate were both increased from M0 to M36 (both P  < .001). Moreover, accumulating recurrence rate was 6.7%, 11.7%, and 17.5% at 1 year, 2 years, and 3 years, respectively. Additionally, anxiety at M24 ( P  = .033), depression at M0, M12, M24, and M36 (all P  < .05) were all correlated with increased accumulating recurrence rate. Continuous monitoring of anxiety and depression might be beneficial for the management of AIS prognosis.